Moringa Oleifera Extract Mitigates Arsenic Trioxide-Induced Gastric Toxicity in Wistar Rats - D. Calmday-Ombo; N. Eluehike (Journal of Applied Sciences and Environmental Management, 2025)
Toxic substances like arsenic trioxide pose a significant threat to gastric health, often leading to severe complications or even death. The search for natural remedies has brought attention to Moringa oleifera, renowned for its medicinal properties and bioactive compounds. Hence, the objective of this paper was to evaluate the protective effects of aqueous extract of Moringa oleifera  on arsenic trioxide-induced gastric toxicity in adult Wistar rats using appropriate standard procedures after treating the Wistar rats with varying concentrations of arsenic trioxide as follows: Group A (control) received only feed and water, Group B was treated with 10 mg/kg arsenic trioxide, Groups C-E received arsenic trioxide plus 200 mg/kg (low dose), 400 mg/kg (intermediate dose), or 800 mg/kg (high dose) of Moringa oleifera, respectively, while Group F received only 800 mg/kg Moringa oleifera. Treatments were administered orally for 28 days. The stomach weight (g) across the different groups was as follows: [A = 1.30 ± 0.25, B = 1.87 ± 0.09, C = 1.33 ± 0.07, D = 1.77 ± 0.20, E = 1.50 ± 0.10, and F = 1.57 ± 0.17 P = 0.1486, P > 0.05], organosomatic index [A = 0.0069 ± 0.0009, B = 0.0071 ± 0.0004, C = 0.0079 ± 0.0004, D = 0.0086 ± 0.0005, E = 0.0089 ± 0.0009, and F = 0.00797 ± 0.0007, P = 0.3180, P > 0.05], initial body weight (g) [A = 174.0 ± 12.64, B = 262.6 ± 9.628, C = 157.7 ± 6.087, D = 180.0 ± 11.87, E = 153.5 ± 8.047, and F = 185.3 ± 13.65. After treatment, the final body weight (g) for the respective groups was [172.4 ± 12.00, 265.2 ± 1.463, 160.6 ± 9.563, 192.2 ± 13.56, 157.6 ± 9.642, and 189.0 ± 10.29] respectively, indicating variations in weight changes across the groups. The statistical values obtained were converted into graphical representation in form of bar charts.  Results showed no significant differences in body weight, organ weight, or organosomatic index across groups. However, histological examination revealed that Moringa oleifera extract provided notable ameliorative and protective effects against arsenic-induced gastric damage. These findings provide evidence of the therapeutic potential of Moringa oleifera in managing gastric toxicity caused by toxicants like arsenic trioxide, offering promise for natural, plant-based interventions.